2019
DOI: 10.3122/jabfm.2019.06.190087
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pre-existing Conditions Among Community Health Center Patients Before and After the Affordable Care Act

Abstract: To assess the prevalence of pre-existing conditions for community health center (CHC) patients who gained insurance coverage post-Affordable Care Act (ACA). Methods: We analyzed electronic health record data from 78,059 patients aged 19 to 64 uninsured at their last visit pre-ACA from 386 CHCs in 19 states. We compared the prevalence and types of pre-existing conditions pre-ACA (2012 to 2013) and post-ACA (2014 to 2015), by insurance status and race/ethnicity. Results: Pre-ACA, >50% of patients in the cohort h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 17 publications
(8 reference statements)
3
22
0
Order By: Relevance
“…24 Huguet et al found a large increase in the prevalence of pre-existing conditions from pre-to post-ACA among CHC patients residing in Medicaid expansion states who were uninsured in the pre-period. 25,26 These findings suggest that a large proportion of conditions were underdiagnosed and undertreated pre-ACA Medicaid expansion due to limited access. Underdiagnosis of chronic conditions has significant health implications: the detection of chronic conditions at the earliest stage possible is critically important to ensure appropriate treatment, decrease risk of complications, and reduce associated costs.…”
Section: Pre-existing Health Conditions Were Diagnosedmentioning
confidence: 96%
See 3 more Smart Citations
“…24 Huguet et al found a large increase in the prevalence of pre-existing conditions from pre-to post-ACA among CHC patients residing in Medicaid expansion states who were uninsured in the pre-period. 25,26 These findings suggest that a large proportion of conditions were underdiagnosed and undertreated pre-ACA Medicaid expansion due to limited access. Underdiagnosis of chronic conditions has significant health implications: the detection of chronic conditions at the earliest stage possible is critically important to ensure appropriate treatment, decrease risk of complications, and reduce associated costs.…”
Section: Pre-existing Health Conditions Were Diagnosedmentioning
confidence: 96%
“…1 Huguet et al assessed the prevalence of pre-existing conditions post-ACA Medicaid expansion among patients who had no insurance coverage in the pre-ACA period, and demonstrated a high prevalence of mental health diagnoses among CHC patients in both states that expanded Medicaid and those that chose not to. 26,28 Mental health disorders were shown to be the most common conditions among CHC patients who gained Medicaid or private insurance following the ACA Medicaid expansion. 26,28 Specifically, the diagnosis with the highest percent increase from pre-to post-ACA Medicaid expansion was a substance use disorder.…”
Section: Mental Health Parity Mattersmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic health record data from over 78,000 uninsured patients aged 19 to 64 years in 386 Community Health Centers in 19 states contain a high level of pre-existing conditions. Huguet et al 20 compared the prevalence and types of preexisting conditions before the Affordable Care Act (ACA) in 2012 to 2013 and post-ACA (2014 to 2015) by insurance status and race/ethnicity. This study emphasizes the high prevalence of pre-existing conditions among Community Health Center patients and the large increase in the proportion of patients with at least one pre-existing condition post-ACA.…”
Section: Social Determinants Of Health-challenges To Best Medical Carmentioning
confidence: 99%